Children with Cerebral Palsy and Their Parents Have Different Experiences of Pain Management: A Qualitative Study - Elisabeth Rønning Rinde; Agneta Anderzén-Carlsson; Reidun Birgitta Jahnsen; Randi Dovland Andersen (MDPI AG, 2024)
Aim: The aim of this study is to explore and compare experiences of pain management strategies for children with CP from the perspectives of children themselves and their parents. Methods: A secondary inductive analysis of previously collected qualitative data was performed. Fourteen children with CP and one parent of each child were interviewed separately about the management of the child's pain. A dyadic data analysis was used to compare parents' and children's perspectives. Findings: The main thematic categories of pain management identified were self-care, psychological strategies, physical interventions and professional treatment. Experiences described by the child and parent differed within all participating dyads but to different degrees. On a group level, children described more use of psychological strategies than parents did. Parents described more professional treatment strategies. Conclusions: Parents and children described different experiences of pain management strategies, and both perspectives are needed to understand the child's situation.